An Introduction to the Angara Lectures of the Family and Welfare Cluster: Focus on Migration - Estrada-Claudio, Sylvia (Review of Women's Studies; Vol 19 No 1-2 (2009): Review of Women's Studies Volume XIX, Numbers 1-2 (January-December 2009), 2023)
This introductory essay serves to introduce the three papers that comprised the feminist research conducted for the research cluster, family and migration. The research was undertaken through the University of the Philippines Center for Integrative and Development Studies and the UPPEJA Research Fellowship.